PENERAPAN LAPORAN KEUANGAN DENGAN METODE RASIO CAMEL UNTUK MENILAI KINERJA KEUANGAN PADA BANK BTN YANG TERDAFTAR DI OJK - RM Bramastyo Kusumo Negoro (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
Banks play an important role in the economy of a country, therefore a healthy bank is needed. Assessment of the health of a bank can be measured using the CAMEL method based on regulations issued by Bank Indonesia No. 6/10/PBI/2004 because Bank Indonesia is the Central Bank whose regulations regulate the Bank Soundness Level. The purpose of this study was to determine the soundness of the State Savings Bank (BTN) in the 2017-2019 period, of which all four were State-Owned Enterprises (BUMN). The research method used is the CAMEL ratio method (CAR, KAP, NPM, ROA & BOPO, LDR). The results of the research for the last 3 years, after being measured by the applicable standard Bank Indonesia regulations, it was found that the average soundness level of Bank BTN was in the Pretty Healthy Predicate. State-owned banks should improve their financial performance to increase the predicate as healthy or very healthy banks because SOEs are banks that have the largest assets in Indonesia